Assessment of knowledge regarding breastfeeding mothers in the immediate postpartum period - Mangalgi, Sharanabasavesh; Sudheendra, Manasa (Indian Journal of Child Health, 2022)
Objectives: To assess the knowledge of mothers regarding breastfeeding in the immediate postpartum period.Materials and Methods: The study was conducted in a tertiary care teaching hospital. The postnatal mothers included in the study were interviewed with a predetermined questionnaire regarding the knowledge of breastfeeding and its importance. Results: A total of 97 mothers were interviewed, of which 69 were delivered normally and 28 by cesarean section. 51 mothers were primigravida and 46 mothers were multigravida. 80 mothers were in the age group of 20-30 years and 34 mothers came from joint family. Around 62.9% mothers had an overall good knowledge score. 100% of the mothers in the study knew the correct position of breastfeeding, 99% of mothers knew breast milk is better than commercial baby food and bottle feeding and had to breastfeed during the night. 96.9% knew they had to inform the doctor about lactation status before obtaining prescriptions for drugs or consumption of drugs. 50.5% had knowledge regarding expressed milk. 35.1% knew about the benefits of breastfeeding to themselves, contraceptive effect of was known in 21.6% mothers. Conclusions: Health-care professionals should ensure proper initiation of breastfeeding following childbirth in all institutionalized deliveries. Irrespective of the parity status, counseling must be provided to all mothers regarding feeding. Knowledge regarding expressed breast milk its technique and storage needs to be impressed on as this becomes a crucial factor in working women.